2020
DOI: 10.1002/adma.202004686
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Oxygen‐Deficient TiO2‐x Nanocrystals for Dual‐Band Electrochromic Smart Windows with Efficient Energy Recycling

Abstract: Dual‐band electrochromic smart windows capable of the spectrally selective modulation of visible (VIS) light and near‐infrared (NIR) can regulate solar light and solar heat transmittance to reduce the building energy consumption. The development of these windows is however limited by the number of available dual‐band electrochromic materials. Here, plasmonic oxygen‐deficient TiO2‐x nanocrystals (NCs) are discovered to be an effective single‐component dual‐band electrochromic material, and that oxygen‐vacancy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 49 publications
4
160
0
Order By: Relevance
“…The coloration efficiency of this film is 37.3 cm 2 c −1 (Fig. S7), which is equivalent to the typical electrochromic properties of TiO 2 [4,8,37]. The high transmittance modulation (77%) and response time (τ b /τ c = 7.9/5.8 s) monitored at 633 nm were also observed (Fig.…”
Section: 5±13 Nmsupporting
confidence: 60%
See 2 more Smart Citations
“…The coloration efficiency of this film is 37.3 cm 2 c −1 (Fig. S7), which is equivalent to the typical electrochromic properties of TiO 2 [4,8,37]. The high transmittance modulation (77%) and response time (τ b /τ c = 7.9/5.8 s) monitored at 633 nm were also observed (Fig.…”
Section: 5±13 Nmsupporting
confidence: 60%
“…The peak area of Zn 2p of the bleached state is far smaller than that of the coloration state, which confirms the (de-)insertion of Zn 2+ . Figure 3b shows that the Ti 2p 3/2 peak at the initial state can be divided into two peaks, corresponding to Ti 3+ 2p 3/2 and Ti 4+ 2p 3/2 , respectively, at 458.5 and 458.9 eV [8,46]. The calculated area ratio of Ti 3+ to Ti 4+ is 1/3, which is consistent with the fact that the TiO 2 matrix remains electrically neutral after Ti is replaced by high valence W. After being fully colored at 0 V, the peak of Ti 2p shifts to higher binding energy.…”
Section: Mechanism Analysis Of Zn 2+ -Based Electrochromic Of W-doped Tio 2 Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] The nonstoichiometric generation of "intrinsic" anion vacancies is also known as a self-doping strategy (Figure 2b). The reported oxygen-deficient NCs, such as WO 3Àx , MoO 3Àx , [59] and TiO 2Àx NCs, [60] belong to this category. In general, these NCs exhibit LSPR absorption properties due to the free electrons released by oxygen vacancies.…”
Section: Overview Of Plasmonic Metal Oxide Ncsmentioning
confidence: 98%
“…Recent studies show a tendency to exploit the properties of TiO 2 at the nanoscale, with significant effects on the performance of EC devices. For instance, Zhang et al [176] reported that oxygen vacancies not only confer good near-infrared transmittance modulation, but also improve lithium diffusion. They obtained TiO 2 nanocrystals capable of modulating the infrared and visible light transmittance independently in three distinct modes, with a modulation of 95.5% at 633 nm and 90.5% at 1200 nm, and fast kinetics.…”
Section: Tio 2 In the Design Of Chromogenic Devices-general Considerationsmentioning
confidence: 99%